Got 15? Try Faculty Development on the Fly: A Snippets Workshop for Microlearning - Carrie Bowler; Cecile Foshee; Faye Haggar; Deborah Simpson; Clara Schroedl; Heather Billings (Association of American Medical Colleges, 2021)
Introduction Faculty development (FD) is an element critical to the professional growth of medical educators and a necessary component in developing effective educators. FD offerings are prevalent across academic institutions; however, faculty report they are unable to participate in these initiatives due to time limitations and competing priorities. The snippet FD approach can address these concerns but requires training for FD providers to be effectively used. Methods This snippet train-the-trainer workshop was presented to approximately 310 physician and nonphysician medical educators at a national medical education conference. The session incorporated multiple teaching modalities (e.g., lecture, demonstrations, structured small-group snippet development groups, and large-group debriefs). A 14-item Likert-scale survey was used to obtain participant evaluations. Narrative feedback was collected using constructed response items. Results Ninety-five percent of respondents (125 of 132) planned to use snippets as an FD strategy at least once per year, with 38% (50 of 132) noting they planned to use snippets at least four times per year. Respondents indicated that FD snippets could positively impact educational practices (94%) and that the session was a valuable use of their time (94%), as well as expressing interest in a snippet repository (90%). Discussion A brief FD train-the-trainer workshop for snippets can successfully prepare FD providers to create and use this approach.